Influence of land use on soil quality and stratification ratios under agro-silvo-pastoral Mediterranean management systems (Agriculture, Ecosystems & Environment, 2014)
a b s t r a c t A case study from north-eastern Sardinia (Italy) in semiarid conditions is presented. Agriculture is mainly extensive and markedly agro-silvo-pastoral, and is typical of similar areas of the Mediterranean basin. The following land uses at different levels of crop intensification were considered: tilled vineyard (TV), no-tilled grassed vineyard (GV), hay crop and pasture with sparse cork oaks (HC and PA), semi-natural systems (SN, former vineyards set-aside about 30 years ago), cork oak forest (Quercus suber L.) established in the past century (CO). Some soil quality parameters were considered: soil organic carbon (SOC) and total N (TN) concentrations, stocks and their stratification ratios with depth (SRs), microbial biomass carbon (MBC) and its quotient to SOC (qmic), and C:N ratios. Both in terms of concentrations and stocks, SOC and TN were generally higher in HC, PA, CO and SN: in these land uses SOC in the topsoil were in the range 17.0–24.3 g kg−1 and 48.9–65.4 t ha−1; TN values were 1.07–2.08 g kg−1 and 3.1–6.0 t ha−1. SOC and TN SRs under the CO land use were higher than 4, quite above the proposed threshold (?2), >2 in GV, and ≥2.0 in PA. MBC in mg kg−1 and qmic in ?g g−1 were higher under CO (194 and 0.89) and GV (156 and 0.97). C:N ratios had optimum or nearly optimum (9–12) values in CO, PA and the GV, in agreement with the SRs, MBC and qmic. A positive and significant correlation was found between SOC and TN concentrations in all the land uses. ©